Digitalization of Labor Migration in the Framework of the EAEU Digital Agenda (International relations and international law Journal, 2025)
The article examines the processes of digitalization of labor migration in the framework of the implementation of the EAEU Digital Agenda, which are becoming particularly relevant in the context of the formation of a single digital space of the union. The purpose of the study is to comprehensively analyze the current state and problems of digitalization of labor migration processes in the EAEU, as well as to develop recommendations for improving the effectiveness of the digital initiatives being implemented.The research methodology is based on a combination of systemic and institutional approaches, includes statistical analysis of data on the functioning of digital services and a comparative analysis of the regulatory framework of the EAEU countries. The empirical base consisted of data on the implementation of the EAEU Digital Agenda, statistics on the use of digital platforms and regulatory acts of the participating countries. The conducted study revealed significant contradictions between the stated goals of digital transformation and the practical results of their implementation. It was found that the effectiveness of existing digital platforms is limited by low user engagement, the lack of uniform standards for electronic document management and an agreed policy for the protection of personal data.The scientific novelty of the study lies in the comprehensive analysis of factors influencing the effectiveness of digitalization of labor migration in the integration association. The practical significance is determined by the developed recommendations for improving the mechanisms of digital transformation, which can be used in the modernization of existing digital services and the formation of a single digital ecosystem of the EAEU labor market.Key words: digitalization, labor migration, EAEU, digital platforms, labor market.